Pengaruh Video Pembelajaran Berbasis Canva Terhadap Hasil Belajar IPAS Materi Atmosfer Bumi Pada Siswa Kelas V Sekolah Dasar - Nuryanti, Yayan; Junarsih, Imas; Heryadi, Yadi (LPPM Universitas Bina Bangsa, 2025)
The development of information and communication technology has driven a transformation in learning strategies in elementary schools, especially through the use of digital media such as Canva. This study aims to determine the effect of the use of Canva-based learning videos on student learning outcomes in the subject of Natural and Social Sciences (IPAS) earth atmosphere material in grade V of State Elementary School 1 Malabar. The research uses a quantitative approach with a quasi-experimental design and a non-equivalent control group design model. The study subjects consisted of 60 students who were divided into experimental and control groups. The instrument used is a learning outcome test in the form of multiplechoice questions that have been validated. The results of the data analysis showed that there was a significant difference between the learning outcomes of students who used Canva-based learning videos and those who used conventional methods, with a significance value (0.00 < 0.05). These findings show that Canva-based learning videos are effective in improving student learning outcomes, as well as students' understanding of abstract concepts in Earth's atmospheric material. This research contributes to the development of interesting and interactive digital learning media, as well as supporting a more meaningful learning process in the digital era.